New chromosome counts in Lythraceae ‑ systematic and evolutionary implications - Graham, Shirley A. (Instituto de Ecología, A.C., 1992)
Chromosome numbers of twenty four taxa in seven genera of the Lythraceae are reported: 16 species and 1 variety of Cuphea\ 2 species of Rotala-, and 1 species each of Diplusodon, Ginoria, Lafoensia, Pleurophora, and Woodfordia. Plant materials originated in México, Guatemala, Ecuador, Brazil, Dominican Republic, Ethiopia, and China. Nineteen counts are first reporte; the others represent populations from geographic areas distant from populations previously counted. Systematic and evolutionary implications of the counts are discussed.